On time, change, history, and conversion - Hannan, Sean (My University, 2020)
Sean Hannan offers a new interpretation of Augustine of Hippo's approach to temporality by contrasting it with contemporary accounts of time drawn from philosophy, political theology, and popular science. Hannan argues that, rather than offering us a deceptively simple roadmap forward, Augustine asks us to face up to the question of time itself before we take on tasks like transforming ourselves and our world. Augustine discovered that the disorientation we feel in the face of change is a symptom of a deeper problem: namely, that we cannot truly comprehend time, even while it conditions every facet of our lives. This book puts Augustine into creative conversation with contemporary thinkers, from Pierre Hadot and Giorgio Agamben to Steven Pinker and Stephen Hawking, on questions such as the definition of time, the metaphysics of transformation, and the shape of history. The goal is to learn what Augustine can teach us about the nature of temporality and the possibility of change in this temporal world of ours.
Keywords: Augustine of Hippo; time; philosophy